- #1

- 655

- 0

Hi, I have to rearrange the formula to get a and b on their own. The real answers are different to mine:

p(a + b) = q (a-b) [a]

pa + pb = qa - qb

pa-qa = -qb - pb

a (p-q) = -qb - pb

a = (-qb - pb)/(p-q)

and the real answer is:

(qb + pb)/(q -p)

it's differnet to mine!

And finding rearranging to get b is

p(a + b) = q (a-b) [a]

pa + pb = qa - qb

pa-qa = -qb - pb

pb + qb = qa - pa

b(p + q) = qa - pa

b = (qa - pa)/(p + q)

and the real answer is

(pa + pa)/(q + p)

Errrrrr!

Can someone so me where i went wrong

Thanks

p(a + b) = q (a-b) [a]

pa + pb = qa - qb

pa-qa = -qb - pb

a (p-q) = -qb - pb

a = (-qb - pb)/(p-q)

and the real answer is:

(qb + pb)/(q -p)

it's differnet to mine!

And finding rearranging to get b is

p(a + b) = q (a-b) [a]

pa + pb = qa - qb

pa-qa = -qb - pb

pb + qb = qa - pa

b(p + q) = qa - pa

b = (qa - pa)/(p + q)

and the real answer is

(pa + pa)/(q + p)

Errrrrr!

Can someone so me where i went wrong

Thanks

Last edited: